Rancang Bangun Sistem Informasi Pelayanan Suku Cadang Motor Pada PT. Kemakmuran Jaya Mandiri - Azis, Bagus Jibrail; Budiman, Ramdani; Hidayanti, Nur; Sujai, Lili (Teknik Informatika Fakultas Ilmu Komputer, 2024)
PT. Kemakmuran Jaya Mandiri Is a company engaged in the sale of Honda motorcycles and service of spare parts.The service information system for motorcycle parts in the company currently uses a combination of spreadsheet technology and records in the customer service book.In addition to the above, an important concern is how the system is able to control every spare parts service data to provide accurate information and can be a control on every replacement transaction and spare parts requests, so that companies have no difficulty evaluating and recording every transaction.The method used to analyze the system that has been running in this company is using the observation method and also direct interviews.Speeds up the service process for replacing spare parts is easier to input and can reduce errors and mistakes. Help the sales counter to record every spare part that has been input and can make more effective reports